Cobalt containing glass fibres and their synergistic effect on the HIF-1 pathway for wound healing applications - Solanki, Anu K.; Autefage, Hélène; Rodriguez, Antonio R.; Agarwal, Shweta; Penide, Joaquin; Mahat, Muzamir; Whittaker, Thomas; Nommeots-Nomm, Amy; Littmann, Elena; Payne, David J.; Metcalfe, Anthony D.; Quintero, Felix; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Chronic wounds are a major healthcare problem, but their healing may be improved by developing biomaterials which can stimulate angiogenesis, e.g. by activating the Hypoxia Inducible Factor (HIF) pathway. Here, novel glass fibres were produced by laser spinning. The hypothesis was that silicate glass fibres that deliver cobalt ions will activate the HIF pathway and promote the expression of angiogenic genes. The glass composition was designed to biodegrade and release ions, but not form a hydroxyapatite layer in body fluid. Dissolution studies demonstrated that hydroxyapatite did not form. When keratinocyte cells were exposed to conditioned media from the cobalt-containing glass fibres, significantly higher amounts of HIF-1α and Vascular Endothelial Growth Factor (VEGF) were measured compared to when the cells were exposed to media with equivalent amounts of cobalt chloride. This was attributed to a synergistic effect of the combination of cobalt and other therapeutic ions released from the glass. The effect was also much greater than the sum of HIF-1α and VEGF expression when the cells were cultured with cobalt ions and with dissolution products from the Co-free glass, and was proven to not be due to a rise in pH. The ability of the glass fibres to activate the HIF-1 pathway and promote VEGF expression shows the potential for their use in chronic wound dressings.